(untitled) (Damascus University Journal for legal sciences, 2024)
Shares with doubled votes lack adequate legal regulation in some legislations, including Syrian legislation, which raised many issues related to defining the components of their existence and clarifying their provisions. This is what lead to application of general rules on these shares in light of this legislative failure, which leads to results that are not commensurate with the nature of these shares. Therefore, these shares have been studied, and what they are in accordance with the existing legal texts, and an attempt to extract the conditions for their existence, determine their nature, and apply general provisions to them in order to reach the weaknesses in this application, and suggest appropriate solutions, with the help of some comparative laws.